INTERNALIZATION OF PRINCIPAL CURRICULUM MANAGEMENT IN PRIMARY SCHOOL AND MADRASAH IBTIDAIYAH - Moh Sholihuddin (The Islamic Education and Multiculturalism Foundation, 2020)
Abstract: Curriculum is a system of learning programs to achieve institutional goals in educational institutions. The purpose of this research is to find out the role of the principal in managing the educational curriculum effectively in the institution. In this study using a literature study method that relies on bibliographic sources from articles in recent journals and books related to the main content of the problem 1) The role of the principal in developing the curriculum include: a) Principal as an educator (Educator), b) Principal as Manager, c) Principal as Administrator, d) Principal as Supervisor, e) Principal as Leader (Leader), f) Principal as Innovator, g) Principal as Motivator. 2) The duties and responsibilities of the principal can be classified into two fields, namely: a) the duties of the principal in the field of administration, including: teaching management, staffing management, discipleship management, building and yard management, financial management, and management of school and community relations. b) the duties of the principal in the field of supervision. Supervision is basically a service provided by the principal to help teachers and employees to become more capable / skilled in carrying out their duties in accordance with the demands of the times